2014
DOI: 10.1016/j.apme.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infection and Immunomodulation: A Possible Explanation for the Hygiene Hypothesis in Autoimmune and Allergic Disease

Abstract: AllergyAutoimmune diseases a b s t r a c t Helminthic parasites have a long history of co-evolution with human beings. The incidence of helminthic infection has significantly decreased in developed countries due to better sanitary measures. However, epidemiological data suggest a corresponding increase in the incidence of autoimmune and allergic diseases in association with a reduction in helminthic infections in these societies. The immune response to helminthic infection involves both innate and adaptive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies have shown that individuals with chronic parasitic infections have lower rates of autoimmune diseases like T1D when compared with those individuals without parasitic infection . Epidemiological surveys have reported that concomitant increase in the prevalence of T1D is associated with reduction in infection rates of humans with helminths . This fact has been tested experimentally in several animal models for autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that individuals with chronic parasitic infections have lower rates of autoimmune diseases like T1D when compared with those individuals without parasitic infection . Epidemiological surveys have reported that concomitant increase in the prevalence of T1D is associated with reduction in infection rates of humans with helminths . This fact has been tested experimentally in several animal models for autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%